Tingkat Kecemasan dalam Menyusun Skripsi pada Mahasiswa Perantau Berdomisili di Yogyakarta - Br. Bukit, Evelynta; Widodo, Yohanes Heri (Universitas Sanata Dharma, 2022)
: This research aimed to: (1) Describe how high the level of anxiety in compiling a thesis on nomadic students domiciled in Yogyakarta, (2) Knowing the item of the anxiety scale item in compiling a thesis identified as not optimal (high) can be proposed as a topic of guidance. This type of research is descriptively quantitative. The subject of this study were nomadic students domiciled in Yogyakarta, totaling 70 people. The data collection used an anxiety scale in the face of a thesis with 52 valid items and had an Alpha Cronbach reliability index of 0.957. The scale is structured based on aspects of anxiety, namely: (1) Physical; (2) Behavior; (3) Cognitive. The data analysis technique used in this study is descriptive statistics that refer to the norms of categorization with: very high, high, medium, low, very low levels. Study results: (1) based on the description of the anxiety level score in compiling a thesis on nomadic students domiciled in Yogyakarta, it was obtained 54,2% with very high category, 35,7% with high category, 7,1% with medium category, 1,4% with low category, and 1,4% with very low category; (2) The results of the item analysis showed 10 items had very high scores. The proposed topics of classical guidance are (1) Rest assured and Believe in yourself, (2) Healthy to succeed, (3) The importance of self-preparation, (4) Understand what is being done, (5) Self-confidence, (6) Managing anxiety, (7) Self-readiness, (8) Stay calm face challenges, (9) How to stay productive, (10) The importance of concentration.